Protection against rabies induced by the non-replicative viral vectors MVA and Ad5 expressing rabies glycoprotein - Garanzini, Debora Patricia (2025)
Rabies is a zoonotic viral disease that is preventable through vaccination. Effective control strategies should follow the “One Health” concept, as targeting zoonotic pathogens at their animal source is the most effective and cost-efficient approach to protecting human health. The aim of this study was to develop and evaluate two third-generation anti-rabies vaccines based on non-replicative viral vectors, MVA and Ad5, both expressing rabies virus (RABV) glycoprotein (MVA-RG and Ad-RG). MVA-RG was produced using a platform developed in our laboratory, while Ad-RG was generated using a commercial kit. Protection against rabies was assessed in a mouse intracerebral (IC) RABV challenge model. Our results demonstrated that both vectors provided protection against RABV. MVA-RG and Ad-RG administered in two homologous doses conferred 60% and 60–100% protection against RABV challenge, respectively. The survival rate was influenced by the viral vector, the dose, and the immunization scheme. Remarkably, to our knowledge, our study is the first to report 100% protection against IC RABV challenge using a non-replicative Ad5 in a homologous immunization scheme. These promising results support future evaluation of this vaccine candidate in target animals.